ASSESSING FINANCIAL FEASIBILITY OF JOINT VENTURE CREATION FOR STEVIA PRODUCTION - Luz Clarita Ina, Felicia
The healthy food and behavior trends have mushroomed in recent years, along with the increase in diabetes patients in Indonesia. PT Mitra Kerinci, a private company in the agriculture industry, aims to supersize the business segments and increasing profit, see a significant opportunity to produce and sell dried stevia leaves through joint venture creation along with the available facilities of 300 Ha land plantation. The lack of knowledge, technology advancement and experience of stevia plantation has driven the management consideration to combining the required resources with another party, PT ABC, in the form of the limited liability company of PT XYZ.The research conducts financial feasibility of PT XYZ to determine the ability of the project in meet PT Mitra Kerinci’s current goals, given that the project potentially incurs huge investment and perform under the profit sharing. Prior to capital budgeting technique assessment, the research will construct pro forma statement and determine capital budgeting cash flow of PT XYZ. Then, four capital budgeting methods that consider time value of money that are Net Present Value, Internal Rate of Return, Discounted Payback Period, and Profitability Index will be used as the evaluation tools of the project. The result of investment through joint venture project will be the most persuasive factor in determining the firm decision to implement the project. The project is expected to generate the Net Present Value of IDR 104,531,609,271 with the internal rate of return is 18.07%. Moreover, the project’s discounted payback period expected to occur in 5 years 7 months 3 days which is less than the project’s designated ceiling of 8 years, and with the profitability index of 2.06. Moreover, the study also involved the risk assessment using the Sensitivity Analysis and Monte Carlo Simulation. The result from the study shows the project is financially feasible with the consideration of sensitive variables in the production process will be faced by the firm that implies the firm should draw much attention regarding the input and the process of plantation. Notwithstanding, there is 7.74% probability of generating the negative return with five sensitive variables of sales price of dried stevia leaves, fresh to dried weight plant ratio, dried leaf to total dried weight plant ratio, the weight of fresh plant and volume stems should be planted per hectare, the project still meets the level of acceptance set by PT Mitra Kerinci.